UPAYA ILO (INTERNATIONAL LABOUR ORGANIZATIONS) DALAM MENGATASI HUMAN TRAFFICKING DI NEGARA-NEGARA ASEAN PADA 2005-2011 - Eka Kurniasari (HI 16 UMY 059, 2016)
*59 ILO or International Labour Organizations is an international organization under The United Nations that works on labour issues. ILO aims at promoting social and economic progress and improving labour conditions. To be able to reach their goals, ILO works with several other international organizations and member states. ILO also has a responsibility to set a standart for labour internationally. The main focus of ILO is the labour or the workers, that’s why ILO applies the tripartite system as the main sytem of ILO’s work. In tripartite system, ILO gathers all the 3 sectors that build industry such as government, employer, and employee. With the gathering of all 3 sectors ILO believe that the opinions of all 3 can make better and fair policy. Nowadays, because of globalizations the crime across the nation border is increasing, not only in numbers, but the form of crimes is diverse. The traffic across the states keep increasing in many form, such as ideas,informations,technology, and even the bad things like drugs and human. Human trafficking is a popular case of international crime. Because of it’s require more than a nation to pevent or against it, it becomes an internastional crime that need an international effort to handle it. Human trafficking happens in many form and forced labour is one of the form of human trafficking. And as an international organizations that works on labour’s safety, ILO show their works on human trafficking. Meanwhile Southeast Asia is one of regions where human trafficking constantly happens. With poverty and, few jobs opportunity, Southeast Asia marked almost 2 million human trafficking cases for a year. And this research will take up ILO’s works on human trafficking in Southeast Asia. Keywords : Human Trafficking, ILO, Southeast Asia